Effect of addition of a starter cultures on physicochemical and sensory properties of "alheira", a smoked sausage-like product - Diana Brito Barros; Cristina Sobrosa; Rita Pinheiro; Susana Fonseca; Manuela Vaz-Velho (Instituto Politécnico de Viseu, 2018)
Introduction: "Alheira" is a traditional Portuguese smoked sausage-like product that can be manufactured with different types of meat and bread. Biopreservation of foods has gained special prominence due to the possibility of naturally controlling the growth of pathogenic and spoilage microorganisms, with a growing interest in the use of lactic acid bacteria (LAB) and their bacteriocins. Objectives: To ascertain the effect of adding fresh and dried starter LAB cultures (Lactobacillus plantarum ST153Ch) on the physicochemical and sensory characteristics of "Alheira". Methods: All samples were produced at the industrial level. Sampling for analytical procedures was performed at 0, 15, 30, 45, 60, 75 and 90 days of storage at 4 C. Physicochemical characteristics (moisture content, pH, water activity (aw), instrumental hardness and adhesiveness, instrumental colour (L*, a*, b*)) and sensory evaluation, performed by 9 panellists regarding visual appearance, odour, texture and taste (11 attributes), were evaluated along the storage at 4 C. Results: Significant differences (p<0.05) were observed in all samples regarding moisture content, pH, aw, instrumental hardness, adhesiveness and in colour parameters, during the storage period. Conclusions: No significant differences in both inoculated "Alheira" samples compared to the control assay were found in sensory analysis until day 90, meaning that L. plantarum ST153Ch starter culture, fresh or dried, could be applied successfully until at least until day 75.